2002
DOI: 10.1007/s00221-001-0992-6
|View full text |Cite
|
Sign up to set email alerts
|

Control of manipulative forces during unimanual and bimanual tasks in patients with Huntington’s disease

Abstract: The aim of the study was to investigate gripload force regulation in Huntington's disease (HD) patients as compared to control subjects during the performance of a manipulative task that required rhythmical unimanual or bimanual isodirectional/non-isodirectional actions in the sagittal plane. Results showed that the profile of grip-load ratio force was characterized by maxima and minima that were attained at upward and downward hand positions, respectively. Minimum force ratio was higher in patients than in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
1
9
1
Order By: Relevance
“…HD patients have previously been shown to have very little deficit in simple bimanual tasks (Johnson et al, 2000;Duval et al, 2009). Rather, they exhibit marked decrease in motor performance as the bimanual task becomes more complex (Johnson et al, 2000;Serrien et al, 2002). Specifically, Brown et al (1993) demonstrated that while HD patients did exhibit deficits in bimanual motor performance, these deficits were smaller than those observed in PD patients.…”
Section: Introductionmentioning
confidence: 87%
“…HD patients have previously been shown to have very little deficit in simple bimanual tasks (Johnson et al, 2000;Duval et al, 2009). Rather, they exhibit marked decrease in motor performance as the bimanual task becomes more complex (Johnson et al, 2000;Serrien et al, 2002). Specifically, Brown et al (1993) demonstrated that while HD patients did exhibit deficits in bimanual motor performance, these deficits were smaller than those observed in PD patients.…”
Section: Introductionmentioning
confidence: 87%
“…Similar to PD and dystonia, HD is associated with elevated grip force levels (Schwarz et al, 2001; Serrien et al, 2001; Serrien et al, 2002a) and slowness of grip force development (Serrien et al, 2001). Grip and load force coupling is also disturbed in HD, and these disturbances increase with task complexity (Serrien et al, 2002a).…”
Section: The Basal Ganglia Are Involved In the Control Of Precisiomentioning
confidence: 99%
“…Excessive GF that is poorly coordinated in time with external load is typical for patients with neurological impairments, such as stroke [16], HungtingtonÕs disease [19], cerebellar lesions [20], cerebellar atrophy [15], or ParkinsonÕs disease [8].…”
Section: Introductionmentioning
confidence: 99%